Advances in the study of B cells in renal ischemia-reperfusion injury - Fan, Hongzhao; Liu, Jia; Sun, Jiajia; Feng, Guiwen; Li, Jinfeng (Frontiers in Immunology, 2023)
Renal ischemia-reperfusion injury (IRI) is a non-negligible clinical challenge for clinicians in surgeries such as renal transplantation. Functional loss of renal tubular epithelial cell (TEC) in IRI leads to the development of acute kidney injury, delayed graft function(DGF), and allograft rejection. The available evidence indicates that cellular oxidative stress, cell death, microvascular dysfunction, and immune response play an important role in the pathogenesis of IRI. A variety of immune cells, including macrophages and T cells, are actively involved in the progression of IRI in the immune response. The role of B cells in IRI has been relatively less studied, but there is a growing body of evidence for the involvement of B cells, which involve in the development of IRI through innate immune responses, adaptive immune responses, and negative immune regulation. Therefore, therapies targeting B cells may be a potential direction to mitigate IRI. In this review, we summarize the current state of research on the role of B cells in IRI, explore the potential effects of different B cell subsets in the pathogenesis of IRI, and discuss possible targets of B cells for therapeutic aim in renal IRI.Renal ischemia-reperfusion injury (IRI) is a common kidney disease that occurs as a result of kidney surgery, cardiac surgery, kidney transplantation, and disruption of the renal blood supply [1]. During renal ischemia, renal tissues are affected by insufficient oxygen supply and accumulation of metabolites, leading to cellular damage and death. Then, the reperfusion process re-inflows blood into the kidney, but causes a series of inflammatory reactions and cellular damage that further aggravates kidney injury [2]. The mechanisms of renal IRI include calcium overload, inflammatory response, reactive oxygen species